A traceable threshold attribute-based signcryption for mHealthcare social network. (2018) - Lu, Yanfei; Wang, Xu; Hu, Chunqiang; Li, Hui; Huo, Yan
With the rapid development of wireless sensor technologies, mobile healthcare social network (MHSN) built upon wireless body sensor network (WBSN), has evolved into an innovative next-generation healthcare system in our aging society. Nevertheless, it is vital to focus on the security issues and the tradeoff between privacy preserving and traceability. A novel security mechanism named as the traceable threshold attribute-based signcryption (TTABSC) can permits patients to be friends and make a proper tradeoff between privacy and traceability. The proposed scheme leverages a four-party model to prevent the leak of a patient's sensitive information, including symptom information, identity and patient's health information (PHI). Combining the digital signatures and encryption, we provide a series of performance analysis, including correctness, unforgeability, traceability and privacy. Compared with previous works, our most efficient scheme generates a constant signcryption size.